Parenting Styles and Dental Caries Among Preschool Children in A Coastal Area of Jember, Indonesia - Elyda Akhya Afida Misrohmasari; Berlian Prihatiningrum (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2022)
Dental caries is a multifactorial condition affected by behavioral factors. Parenting styles reflect different behavior influenced by cultural and socioeconomic backgrounds. Coastal areas have unique cultural and socioeconomic conditions and underlie the community's upbringing behavior. This study aims to determine the differences in preschool children's caries experience based on parenting patterns in a coastal area. This study is a cross-sectional study on children and their parents in the coastal area of Puger, Jember, East Java, Indonesia. The participants were 269 pairs of preschool children and parents selected by random cluster sampling. The dependent variable was dental caries experience measured using the def-t index. The independent variable was the type of parenting categorized into three groups (authoritative, authoritarian, permissive) based on a questionnaire distributed to parents. The Kruskal-Wallis test was applied to determine the difference in caries rates in each parenting style (p≤ 0.05). The results showed that the prevalence of primary teeth caries was 97%, and the mean of def-t was 10.03. Authoritative parenting style was the majority (81.8%), and no statistically significant difference was found between caries and parenting style (p=0.473). However, the mean of def-t in the authoritarian group was higher than in others (10.42). Based on the result, it can be concluded that mean of dental caries among children in a coastal area with authoritarian parents was the highest one compared to others, but the difference was statistically insignificant.